Distinguished ground improvement projects by dynamic compaction or dynamic replacement - Hamidi, Babak (Curtin University, 2014)
Dynamic compaction is a popular ground improvement technique, and has been the subject of various research. However consolidated and comprehensive information on the subject is outdated, and publications remain scattered. In this thesis previously published researches have been collected, reviewed, commented on and compiled into a thorough and comprehensive document. Additionally, previously unpublished state-of-the-art dynamic compaction projects have been described, reviewed, analysed, compared with earlier research, and new formulations and calculation methods have been developed.